The Effectiveness of Classical Music Therapy in Relation to Anxiety Levels of Pregnant Women at Pratik Mandiri Midwife Puspitarini, A.Md.Keb Glenmore District - Febrika Devi Nanda (Yayasan Cendekia Gagayunan Indonesia, 2025)
Pregnancy is the intrauterine growth and development of the fetus starting from conception and ending until the start of labor. The length of pregnancy from ovulation to parturition is approximately 280 days (40 weeks), and no more than 300 days (43 weeks). Anxiety is a response to certain threatening situations and is a normal thing that occurs accompanying development, change, and in finding one's identity and the meaning of life. One way to deal with anxiety is non-pharmacological therapy, namely distraction techniques. This research uses a quasi-experimental research design with a One Group Pretest-Posttest Design research design. This research was conducted to determine the effectiveness of providing classical music therapy to reduce anxiety levels in pregnant women.That before classical music therapy was given a non-anxious level of anxiety, namely 9 respondents (16.7%), a moderate level of anxiety, namely 8 respondents (16.7%). Then, after being given classical music therapy, the majority of respondents had a non-anxious level of anxiety, namely 20 ( 66.7%) The level of mild anxiety was 10 respondents (33.3%). The pre-test and post-test show a significant relationship with the criteria for the level of anxiety of pregnant women with a p value = 0.000, <0.05 N = 30, so it can be concluded that there is a significant effect of effectiveness between classical.